Prognostic and Predictive Biomarkers in Gastroenteropancreatic Neuroendocrine Tumors - Stevenson, Ryan; Libutti, Steven k; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2013)
Neuroendocrine tumors (NET) are a diverse group of tumors that derive from epithelial cells with neuroendocrine differentiation. Gastroenteropancreatic NETs are a subset of NET that arise from the gastrointestinal tract. The natural history and prognosis varies widely between different gastroenteropancreatic NETs, highlighting the importance of identifying accurate prognostic and predictive biomarkers. At the 2013 ASCO Gastrointestinal Cancers Symposium, De Braud et al. (Abstract #186) and Bellister et al. (Abstract #163) present data on two new possible biomarkers. Image: Logo (Tufts Medical Center. Boston, MA, USA).